Comprehensive Evaluation of Different Oat Varieties in Semi-Arid Areas of Gansu Province - Guanlu Zhang; Jikuan Chai; Guiqin Zhao; Liang Zeng; Wenping Wang; Kuiju Niu (Agronomy)
In light of the current global challenges, such as climate change, the overexploitation of natural resources, and increasing food demand, drought-tolerant forage crops present substantial potential for development in dryland regions. However, there is a notable gap in research that integrates yield improvement, nutritional quality enhancement, and resistance to pests and diseases in the production of forage crops in semi-arid areas. Therefore, selecting oat forage varieties that exhibit high yield, superior quality, and enhanced pest resistance can substantially advance the forage industry and animal husbandry in semi-arid regions. In this study, ten oat varieties, including both domestic and international cultivars, were cultivated in a semi-arid region (Weiqi town, Gansu Province) during the 2023–2024 growing season. A comprehensive analysis was performed to assess the yield, quality, and pest resistance of these varieties. All ten oat varieties successfully completed their growth cycles. Among them, Everleaf 126 exhibited a shorter plant height compared to the other varieties, measuring 103.32 cm and 115.14 cm over two years. However, its superior leaf area and tiller number led to the highest hay yields (11,819.33 kg/ha and 13,550.67 kg/ha) and seed yields (4913.20 kg/ha and 5242.33 kg/ha). Additionally, Everleaf 126 demonstrated significantly higher leaf–stem ratios (0.35 and 0.41), crude protein content (8.52% and 9.13%), and crude fat content (2.19% and 2.69%) relative to other oat varieties (p < 0.05). Furthermore, it showed the best resistance to powdery mildew (MR), red leaf disease (HR), leaf spot disease (MR), and aphids (R). The plant height of Kona was the lowest, measuring 81.22 cm and 87.16 cm, respectively, with the fewest number of tillers and the smallest leaf area. Baler II exhibited the lowest hay yield at 8770.10 kg/ha and 7898.33 kg/ha, as well as the lowest seed yield at 3409.33 kg/ha and 3323.90 kg/ha. Kona also had the lowest leaf–stem ratio (0.19 and 10.13) and crude protein content (5.74% and 6.58%), while exhibiting the highest neutral detergent fiber (NDF) and acid detergent fiber (ADF) values. Furthermore, Kona showed the poorest resistance to powdery mildew (MS) and leaf spot (MS). Finally, based on the comprehensive evaluation analysis of the membership function, in the semi-arid region, Everleaf 126 achieved the highest overall performance based upon a comprehensive evaluation, followed by Molasses and Longyan No.3. In comparison, Kona received the poorest performance.